Knowledge and perception about generic drugs in patients coming to OPD of tertiary care centre - Choulera, Mehul Y.; V., Dashputra Amruta; Borkar, Archana S.; Date, Amit P. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In an era of rapidly rising health care costs generic medicines provide a less expensive alternative to branded medicines. In addition to reducing the overall health care expenditure, it has been shown to improve adherence. Objective was to study knowledge and perception about generic drugs among patients coming to outpatient department of tertiary care centre. Methods: After ethical approval a cross sectional questionnaire based study was conducted. Patients (n=71) were interviewed according to questionnaire in vernacular language by investigator to fill questionnaire. Results: About 28% people think that price of generic drug is less than a branded drug while nearly 61% of people don’t know of it. Only 18.85% participants had taken generic medicine. Trusting efficacy of generic drugs only 30 participants were in favour it. Even they have not seen or heard publicity of generic drugs (61.97%). They (60.56%) opined that generic drugs never prescribe in our country. Conclusions: Limitation in knowledge and perception about generic medicines has been seen among participants.